Reactive oxygen species and nitric oxide affect cell wall metabolism in tobacco BY-2 cells - Pacoda, Daniela (Journal of plant physiology, 2004)
The effects of hydrogen peroxide (H2O2), nitric oxide (NO), and a combination of both on the metabolism of cell wall polysaccharides were studied in tobacco (Nicotiana tabacum L.) cv Bright Yellow 2 (BY-2) suspension cultured cells in the presence of D-[U-14C]glucose or D-[U-14C]galactose as radioactive tracers. We found that the radiolabelling of newly synthesised total cell wall polysaccharides (pectins, hemicelluloses and alpha-cellulose), buffer-soluble polysaccharides, and membrane-associated polysaccharides decreased under the influence of exogenous systems generating H2O2 and NO. However, when the total amount of newly synthesised cell wall polysaccharides was calculated as a percentage of the total cellular radioactivity (ethanol-soluble pool plus the homogenate of ethanol-insoluble material), all treatments showed negligible effects in the presence of D-[U-14C]glucose or D-[U-14C]galactose as tracers. This occurred because the treatments generating H2O2, NO and H2O2 plus NO caused a marked decrease in the concentration of the ethanol-soluble pool as well as in the total radioactivity found in the homogenate of the ethanol-insoluble material. Most of the radioactivity taken up by the cells was evolved as 14CO2 during the respiratory processes. A qualitative and quantitative characterisation of the ethanol-soluble pool showed that radioactive UDP-sugars in BY-2 suspension cultured cells were differentially reduced by all treatments. Therefore, the decrease of the newly synthesised cell wall polysaccharides seems to be strictly dependent on the reduction of the UDP-sugars pool